Faktor-Faktor yang Mempengaruhi Konsumen dalam Pembelian Jajanan Tahu Walik di Kota Cianjur - Augustian, Billy; Jesica, Camila Nadya; Nasri, Kimberly; Utami, Nabilah Wahyu; Hoetama, Pedro; Widjaja, Samuel; Marchalina, Leonis (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
As time goes, Small Medium Enterprise (SME) has grown so fast, especially at Cianjur. Culinary is well-known as biggest contributor for the SME at Cianjur. PKM is a program that support economic growth at Cianjur, which also raise awareness and sales. There are 4 factors that elevate the SME at Cianjur, which is operation, marketing, financing, and human resource management. This research focus on marketing. This research exists to support the growth of Tahu Walik Si Montogh to become a great business. The rise of Tahu Walik Si Montogh can be achieved by choosing the right segmentation, positioning, and target, which based on consumer behaviour in Cianjur. Branding strategy for Tahu Walik Si Montogh use stimulus response approach, and persuasive communication technique that is also based on segmentation, positioning, and target, which has been defined previously and can be the base of marketing strategy for Tahu Walik Si Montogh. These two strategies are also supported by increasing the product diversification to attract customer in Cianjur.